Craniofacial anthropometry, skull bone thickness and intracranial volume changes in epileptic patients - Shirin, Lubna (2022)
Epilepsy is a genetic and neurological disorder. Prolonged use of anti-epileptic drugs causes atypical facial shape, facial coarsening, gingival hyperplasia, gum hypertrophy. Many studies were done on craniofacial dimensions, skull bone thickness (SBT), and intracranial brain volume (ICV) in normal populations of different countries and races and different disorders, but very few references were found on epilepsy patients. The present study examined craniofacial anthropometry, SBT, and ICV in male and female epilepsy patients in Malaysia, it could aid with a better care approach for them. A retrospective study was done using data from epileptic patients from 2010-2017 who were under medication for five years as well as data from control subjects were selected who had their computed tomography (CT) scan at the Radiology Department, Hospital Universiti Sains Malaysia (HUSM). A total of 200 CT data of 18-60 years of age of both gender were collected from the archive 2010-2017 duration with permission for this study. Based on the inclusion criteria, subjects involved in this study were divided into epilepsy and control groups of both genders in anthropometric dimensions (male n= 14, female n= 15), SBT (male n= 17, female n= 15), and ICV (male n= 17, female n= 15) estimation. Other CT data were excluded based on exclusion criteria. Data measurements were carried out in the School of Dental Science, USM. A 3D CT scan was used for the measurement of both craniofacial and SBT by using MIMICS software and MITK 3M3 software was used for ICV measurement. Twenty parameters were used for craniofacial anthropometry measurements. SBT was measured at three levels; at glabella, at bregma, and in between the two. The internal consistency level was determined by three raters for craniofacial and SBT, and two raters for ICV measurements. In the craniofacial measurement, epileptic males showed significantly higher measurements in nasion_bregma (n_br) and lower measurements in the mid zygomatic arch to mid zygomatic arch (zy_zy)), nasion to alveoli (na_al), superior nasal width right to left (snmr.r-snmr.l), superior zygomatic width right to left (zt.r_zt.l), inferior zygomatic width right to left (zti.r_zti.l) compared to the control group. Anterior-superior orbital ridge right to left (sor.r_sor.l) was significantly higher and superior zygomatic width right to left (zt.r_zt.l) was significantly lower measurements in epileptic female than the control. Regarding craniofacial anthropometry, the study can conclude epilepsy might have effects on some facial and cranial bones but not on all areas in both genders. For SBT, the male group did not show any significant difference but epileptic females showed significantly higher measurements in glabella_bregma. It can determine that epilepsy may not have an effect on male skull bone but can produce an effect on female skull bone.ICV did not reveal any significant differences between epileptic and control groups and epilepsy might not have any effect on ICV of both genders. The current findings in the epileptic group could be attributed to the effects of anti-epileptic medicines particularly in the treatment of epileptic populations. Furthermore, this reference data will be a valuable resource for craniofacial researchers as well as medical experts in the future for the betterment of their lives.